Effectiveness of Self-instructional Module on Knowledge Regarding Prevention of Surgical Site Infection among Postoperative Cardiac Patients: A Research Protocol - Shiwani Padmakar Dandade; Arati Raut (Journal of Clinical and Diagnostic Research)
Introduction: Heart failure, often known as congestive heart failure or congestive cardiac failure, is a common, expensive, debilitating, and potentially fatal condition that arises when the heart is unable to produce enough pump action to sustain blood flow to meet the body’s needs. An integral part of managing cardiovascular risk is leading a healthy lifestyle. Need of the study: Surgical Site Infections (SSI) in cardiac surgery remain a significant medical problem due to the deteriorated postoperative quality of life, increased mortality, more extended hospital stays, and increased treatment costs. Aim: The present study aims to evaluate the effectiveness of Self-Instructional Modules (SIM) on knowledge regarding the prevention of SSI among postoperative cardiac patients. Materials and Methods: A quasi-experimental research design (one group pretest, post-test research design) will be conducted at AVBRH Sawangi (Meghe), Wardha, Maharashtra, India from March 2024- March 2025. A total of 140 subjects will be included in the study. A structured questionnaire based on the knowledge will be used to assess the effectiveness of the SIM on the prevention of SSI. The tools will consist of Section-I: Demographical data like age, gender, family income, occupation, education, stay in the hospital after surgery, and the type of cardiac surgery. Section-II: Structured knowledge questionnaire on the prevention of SSI among postoperative cardiac patients. A SIM will be provided to the postoperative cardiac patients regarding the prevention of SSI. One-way ANOVA will be applied to statistically evaluate the association of demographic variables with the level of knowledge regarding the prevention of SSI. A paired t-test will be used for the pre and post-test evaluation of the participants. A p-value of <0.05 will be considered significant.